Gametogenesis in Plasmodium: Delving Deeper to Connect the Dots - Dash, Manoswini; Sachdeva, Sherry; Bansal, Abhisheka; Sinha, Abhinav (Frontiers in Cellular and Infection Microbiology, 2022)
In the coming decades, eliminating malaria is the foremost goal of many tropical countries. Transmission control, along with an accurate and timely diagnosis of malaria, effective treatment and prevention are the different aspects that need to be met synchronously to accomplish the goal. The current review is focused on one of these aspects i.e., transmission control, by looking deeper into the event called gametogenesis. In the Plasmodium life cycle, gametocytes are the first life forms of the sexual phase. The transmission of the parasite and the disease is critically dependent on the number, viability and sex ratio of mature gametocytes and their further development inside mosquito vectors. Gametogenesis, the process of conversion of gametocytes into viable gametes, takes place inside the mosquito midgut, and is a tightly regulated event with fast and multiple rounds of DNA replication and diverse cellular changes going on within a short period. Interrupting the gametocyte-gamete transition is ought to restrict the successful transmission and progression of the disease and hence an area worth exploring for designing transmission-blocking strategies. This review summarizes an in-depth and up-to-date understanding of the biochemical and physiological mechanism of gametogenesis in Plasmodium, which could be targeted to control parasite and malaria transmission. This review also raises certain key questions regarding gametogenesis biology in Plasmodium and brings out gaps that still accompany in understanding the spectacular process of gametogenesis.